Poetry, dramaturgy and counterwriting in La soledad de Asterión by Santiago de Luca - Moreno del Cristo, Aluned (Amaltea. Revista de Mitocrítica, 2026)
La soledad de Asterión: pieza teatral en nueve curvas (2019), by the Argentine writer Santiago de Luca, rewrites the myth of the Minotaur in contemporary Latin American theater. This play establishes explicit links with the work of Borges and possesses a poetic tone in many passages, evident through the use of various literary devices and metaphorical language. This relationship is also evident in the way De Luca delves into the subjectivity of the Minotaur. Thus, the objective of this essay is to analyze the connections that can be found between the work of Santiago de Luca and that of Borges, in order to elucidate to what extent the interconnection between literary genres and counter-scriptural procedures allow the contemporary play to carry out a creative transformation of the myth and, at the same time, productively dialogue with Borges’s work.